Association between violent behavior and psychotic relapse in schizophrenia: once more through the revolving door? - Ana Fresan (Salud Mental, 2007)
The potential for violence in a number of persons with mentalillnesses stimulates public fear and prevents general acceptanceof persons with psychiatric disabilities.Schizophrenia has been the diagnosis most often associated withviolence as it has been taken as a paradigm of insanity, incompetenceand dangerousness.Clinicians efforts to prevent violence through conventionalexternal patient treatment are impede by several situational variablesand patients become trapped in a costly cycle of repeatedinstitutional admissions (revolving door phenomenon) in the mostrestrictive settings, going through involuntary in-patient treatment.The major hypothesis proposed in this review is that violencein schizophrenia can become a part of a self-perpetuating cycle,in which the combination of non-adherence to treatment and aninadequate management of illness from families and caregiversleads to violent behavior and deteriorated social relationships, finallyresulting in institutional recidivism.As some of the initial symptoms of the illness, such as irritabilityand agitation may not be detected by the patient and his/herfamily, these symptoms eventually can easily escalate into openhostility, and the accompanying behavior is frequently violent.Disturbed moods secondary to psychotic symptoms, such asfear and anger apparently can also activate violent psychotic action.Accordingly, the path from the characteristics of the illnessto violence leads to them through psychotic symptoms and lackof insight, and results in symptom-consistent violence.